Development of autonomous mobile robot navigation system using RFID - Hossain, Mahbuba (Kulliyyah of Engineering, International Islamic University Malaysia, 2015)
Navigation techniques in mobile robotics system have gained significant research interest over the past few years. The mobile robot must be able to navigate through a known or unknown environment based on its necessities and applications. This can be achieved by determining its positions and selecting a suitable motion control. Conventional techniques include landmark or dead-reckoning with excessive number on sensors which increases complexities. Several other researchers have been done using both active and passive Radio Frequency Identification (RFID) Signal but there is still need for a more simple and suitable navigation system. This research has been done to present an effective navigation technique using passive RFID reader and tags. The proposed algorithm provides not only the estimation of the robot position in the environment but also the orientation of the autonomous robot. Polar coordinate system has been adopted on the navigation environment where the RFID tags are placed in a grid-like pattern with constant distance. The research objectives have been fulfilled via simulation and experimental validation through hardware implementation. The experimental results show effective and reliable results and the novelty lies in the use of simple technique to achieve the objectives. As a whole, this work has investigated and analyzed several navigation techniques and adopted the best technique for practical application with satisfactory results.